{Catalytic Ferrier rearrangement of unsaturated nucleosides} - Linker, T; Sommermann, T; Gimisis, T.; Chatgilialoglu, C (Tetrahedron Lett., 1998)
The attempted intermolecular addition of malonyl radicals to 1',2'-unsaturated nucleosides has led to the unexpected formation of furanones. Thus, only catalytic amounts of ceric(IV) ammonium nitrate (CAN), induce a Ferrier rearrangement. The unsaturated lactone was isolated in good yield and can serve as a precursor for the synthesis of optically active products. (C) 1998 Elsevier Science Ltd. All rights reserved.